간호대학생의 동영상을 활용한 방사선안전관리 교육의 효과 - 윤영숙(Young Suk, Yoon) (한국간호연구학회지, 2019)
Purpose : This study is to promote awareness to be exposed to radiation with identifying effect of radiation safety management(RSM) education with the use of visual-auditory materials for nursing students. Methods : The subjects were 122 of the nursing students and this study performed a questionnaire survey 25 March to 17 April, 2019. Results : As a result of examining the knowledge level of RSM, the average correctness rate of knowledge before training was 44.7% and the rate of correcting after training was 76.5%, which was significant(t＝ -16.71, p＜.001). As a result of examining the level of attitude toward RSM, it was 3.90±.75 points before training and 4.29±.72 points after training, which was a significant difference(t＝-6.20, p＜.001), and the radiation anxiety score was 3.11±.67 before training and 3.09±.72 after training, which was no statistically significant( t＝-.23). The RSM knowledge score showed a statistically negative correlation with radiation hazard anxiety score(r＝-.23, p＝.010). Conclusion : We believe that a variety of programs should be offered to provide knowledge on RSM as a prerequisite for improving the level of RSM by nursing student. KCI Citation Count: 0